Evaluacion fisicomecanica de la pulpa kreft blanqueada de la madera de Pinus douglasiana Martinez - Rutiaga Quiñones, J.G.=700 1 Rivera Prado, J. de J.; Sanjuan Dueñas, R.
(Es, En)
Ilus., 22 ref.
Keywords: PINUS; PROPIEDADES FISICOQUIMICAS; PROPIEDADES MECANICAS; PULPA DE MADERA; BLANQUEO; MEXICO; PINUS DOUGLASIANA; PULPA KRAFT